8 - African Elites and their Post-colonial Legacy: Cultural, Political and Economic Discontent – by Way of Literature - Diop, Samba (Africa Development, 2021)
In this article, I propose to discuss the way in which the issues of post- colonial modernism in the context of neoliberal capitalism has impacted on the traditional cultures and economic life of Africa’s new classes. These include the bureaucratic and professional classes and the materially less fortunate members of the other post-colonial classes. In this regard I choose to examine, specifically, the way in which cultural traditions and modernity exist in an uneasy symbiosis under the powerful influences of contemporary political economy. Normally, when one speaks of the economics of Africa, it is usually done at a distance, with numbers and charts reflecting GDPs, growth rates, per capita incomes, etc., all in the context of ministrations from institutions such as the IMF and the World Bank. Unless one were directly involved it would be difficult to grasp the impact of the structural adjustments imposed on Africa’s peoples as they struggle to partake of the material life engendered by modern capitalism. The struggle is about maintaining statuses of economic materiality within a cultural context of eroding traditions. In this struggle to partake of modernity, as determined by the dictates of modern capitalism, the sociological results are a minority of economically well-off individuals, but with the masses of the people increasingly impoverished in a continent rich in natural resources and development potential. In sum, the theme of this is Africa’s cultural and economc discontent in an age of an essentially unchallenged neoliberal capitalism.